Estimation algorithm of information significance and authenticity of labor protection at an enterprise - Ревук, О. Г.; Кружилко, О. Є.; Гулевець, В. Д. (Proceedings of National Aviation University (archive), 2000)
Proposed is a mathematical model which can be efficiently applied not only to optimization of resources distribution for labor protection needs and designation of measures for future period but also for information authenticity and significance to be used for taking management decisions. Complex of mathematical models describing various indexes and processes controlling labor protection constitute the basis for taking decision